Replication kinetics of turkey herpesvirus in lymphoid organs and feather follicle epithelium in chickens - OTOMO, Hiroki; TANENO, Akira; OKURA, Takashi; OISHI, Eiji (Journal of Veterinary Medical Science, 2021)
Marek’s disease virus (MDV) is an oncogenic alphaherpesvirus that causes immunosuppression, T-cell lymphomas, and neuropathic disease in infected chickens. To protect chickens from MDV infection, an avirulent live vaccine of turkey herpesvirus (HVT) has been successfully used for chickens worldwide. Similar to MDV for natural infection in both chickens and turkeys, HVT also infects lung in the early stage of infection and then lymphocytes from lymphoid organs. Virus replication requires cell-to-cell contact for spreading and semi-productive lytic replication in T and B cells. Then, cell-free infectious virions matured in the feather follicle epithelium (FFE) are released and spread through the feather from infected turkeys or chickens. To understand the lifecycle of HVT in inoculated chickens via the subcutaneous route, we investigate the replication kinetics and tissue organ tropism of HVT in chickens by a subcutaneous inoculation which is a major route of MDV vaccination. We show that the progeny virus matured in lymphocytes from the thymus, spleen, and lung as early as 2 days post-infection (dpi) and bursa of Fabricius at 4 dpi, whereas viral maturation in the FFE was observed at 6 dpi. Furthermore, semi-quantitative reverse transcription-PCR experiments to measure viral mRNA expression levels revealed that the higher expression levels of the late genes were associated with viral maturation in the FFE. These data that tropism and replication kinetics of HVT could be similar to those of MDV through the intake pathway of natural infection from respiratory tracts.